Transacciones Comunicativas y Estructuración de Límites en Familias Reconstituidas Desde la Perspectiva del Hijo Adolescentes (2024)
The present investigation has as purpose to investigate the concepts that the adolescent in relation to the communicative transactions and the establishment of the limits within the reconstituted family. To this end, social constructionism based on narratives and a qualitative methodological framework were used as an epistemological basis, using narrative resources, through a story or stories that will be obtained through an open interview, for later analysis of the results.